Empirical correlates of cosmopolitan orientation: Etiology and functions in a worldwide representative sample - LIU, James H. (Institutional Knowledge at Singapore Management University, 2020)
Psychology has begun contributing to social theory by providing empirical measures of actually existing cosmopolitanism that complements more purely theoretical conceptions of the construct common in philosophy and sociology. Drawing from two waves of research on representative adult samples from 19 countries (N = 8740), metric invariance was found for the three factors of cosmopolitan orientation (COS): cultural openness (CO), global prosociality (GP), and respect for cultural diversity (RCD). In terms of etiology, among Wave 1 measures, the personality factor of agreeableness was the best predictor of the cosmopolitan factors of GP and RCD at Wave 2, whereas openness of personality best predicted CO. Wave 1 measures of education, political liberalism, and self-reported social status independently also explained a small amount of variance in COS. Functionally, COS was shown to predict less prejudice against immigrants, and more support for global civil society, even after controlling for social dominance orientation. All three COS factors independently predicted better attitudes towards immigrants. GP was the best predictor of trust in the United Nations, whereas RCD was the best predictor of support for environmental protection. The three-factor model of COS appears well-calibrated for assessing actually existing cosmopolitanism across cultures.